A Study Of Kindergarten's Self-learning Tools To Read Jawi Using Mobile Application - Noorrezam Yusop; Mohd Naser Mohd Sabri (ASIAN SCHOLARS NETWORK, 2024)
Jawi is a script based on the writing of the Al-Quran and derived from Arab-alphabet characters. When reading and writing religious books, stories, and so on, Jawi script is essential. However, in order to understand Jawi, students must first learn how to read Jawi, which should begin in kindergarten. They must be able to identify characters in Jawi. As a result, this paper addresses a research gap for existing work on learning Jawi script that is available in the market for commercial and scientific uses of mobile applications. We present our findings through a review and analysis of several studies. The features' and utility's strengths and shortcomings are also offered to provide a better knowledge of the gaps and weaknesses of each tool.